2024
DOI: 10.2138/am-2023-8963
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing volatile exsolution in a porphyry ore-forming magma chamber: Perspectives from apatite inclusions

Wenting Huang,
Michael J. Stock,
Paul C. Guyett
et al.

Abstract: Porphyry-type deposits in the shallow crust (3-5 km) are formed from metal-rich fluids exsolved from underlying magma chambers (5-15 km). However, a direct volatile record of the fluid exsolution in the magma chamber is commonly lacking.Here, we analyse the compositions of apatite inclusions (in biotite and plagioclase phenocrysts, and fully-/partly-included in zircon microphenocrysts) and the apatite in groundmass from the largest Cretaceous Luoboling porphyry Cu-Mo deposit in South China. In combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…The S (0.02-0.56 wt% SO 3 ) and Cl (0.01-0.58 wt% Cl) in apatite from the Delamerian porphyry systems are significantly lower than those from porphyry deposits in subducted magmatic arcs (normally 0.12-0.60 wt% SO 3 and 0.2-3.0 wt% Cl). Recent studies have shown that zircon-hosted apatite inclusions prior to volatile exsolution commonly contain relatively high magmatic Cl and SO 3 contents essential to potential porphyry Cu-Mo ± Au mineralization Huang et al 2024). All the apatite crystals analyzed in this study were separated and hand-picked from intrusive rocks and they probably occur as microphenocrysts in groundmass or as inclusions hosted by plagioclase and biotite.…”
Section: Moderately High Oxidationmentioning
confidence: 96%
See 1 more Smart Citation
“…The S (0.02-0.56 wt% SO 3 ) and Cl (0.01-0.58 wt% Cl) in apatite from the Delamerian porphyry systems are significantly lower than those from porphyry deposits in subducted magmatic arcs (normally 0.12-0.60 wt% SO 3 and 0.2-3.0 wt% Cl). Recent studies have shown that zircon-hosted apatite inclusions prior to volatile exsolution commonly contain relatively high magmatic Cl and SO 3 contents essential to potential porphyry Cu-Mo ± Au mineralization Huang et al 2024). All the apatite crystals analyzed in this study were separated and hand-picked from intrusive rocks and they probably occur as microphenocrysts in groundmass or as inclusions hosted by plagioclase and biotite.…”
Section: Moderately High Oxidationmentioning
confidence: 96%
“…Cl and SO 3 contents than those hosted by zircon, due to fluid exsolution or re-equilibrium with post-exsolution melt (e.g., Sun et al 2023;Huang et al 2024). This is one of the likely reasons that apatites from the Delamerian porphyry prospects have significantly lower S and Cl signatures than those from typical porphyry Cu deposits in magmatic arcs.…”
Section: Sulfur and Chlorine Contentsmentioning
confidence: 99%